Effect of surrounding landscape on Popillia japonica abundance and their spatial pattern within Wisconsin vineyards - Henden, Jacob; Guédot, Christelle (Frontiers in Insect Science, 2022)
Landscapes surrounding agroecosystems can provide resources that may benefit insect pests. This project examined the influence of the surrounding landscape on the abundance and spatial pattern of Popillia japonica (Coleoptera: Scarabaeidae) in vineyards. Twenty vineyards across Southern Wisconsin, spanning a gradient of 5-80% cropland in a 1.5km radius surrounding landscape, were sampled in 2017 and 2018 for P. japonica adults and leaf injury. The distribution of P. japonica and leaf injury was assessed by sampling along a transect at the edge, halfway from the edge to the center, and at the center of each vineyard. The proportion of cropland and pasture in the surrounding landscape along with abiotic factors of temperature, precipitation, longitude, and pesticide use (determined using Environmental Impact Quotient) were included in models to explain the variation of P. japonica abundance and leaf injury. No significant relationship was observed between proportion cropland in the surrounding landscape and P. japonica abundance or leaf injury. Combined effects of pasture, longitude, and temperature best explained variation in the abundance of P. japonica adults while longitude, temperature and EIQ best explained variability in leaf injury. Vineyards with more pastures in the surrounding landscape, located further east, and with higher temperatures, generally had more P. japonica adults and vineyards further east with higher temperature and lower EIQ pesticide use generally had higher levels of leaf injury. Additionally, variability in weekly temperature and precipitation influenced weekly abundance, with higher temperatures and less precipitation resulting in greater weekly abundance of P. japonica adults. Significantly more adult P. japonica and greater leaf injury were found at the edges than in the center of vineyards. Our results suggest beetles from the surrounding landscape likely contribute to populations of P. japonica adults found feeding on vines on vineyard edges, and P. japonica abundance and associated leaf injury are influenced by geographical location, local weather conditions, and pesticide use.